Evaluation of the adequacy of phase equilibria modeling based on various sets of experimental data - A. V. Frolkova; V. G. Fertikova; E. V. Rytova; A. K. Frolkova (Тонкие химические технологии)
Objectives. The purpose of the paper is to compare the adequacy of mathematical models of vapor–liquid equilibrium (VLE) and their ability to reproduce the phase behavior of the ternary system benzene–cyclohexane–chlorobenzene using different experimental data sets to evaluate binary interaction parameters.Methods. The research methodologies were mathematical modeling of VLE in the Aspen Plus V.10.0 software package using activity coefficient models (Non-Random Two-Liquid (NRTL), Wilson) and the Universal quasichemical Functional-group Activity Coefficients (UNIFAC) group model, which allows for independent information. For the benzene–cyclohexane–chlorobenzene ternary system, the use of the NRTL equation is warranted because it provides a better description of the VLE experimental data.Results. The diagram construction of the constant volatility of cyclohexane relative to benzene lines revealed three topological structures. Only one of them can be considered reliable because it corresponds to the experimental data and coincides with the UNIFAC model diagram constructed based on independent UNIFAC model data. The results indicate that to study systems containing components with similar properties, it is necessary to improve the description quality of the available data sets (the relative error should not exceed 1.5%).Conclusions. The reproduction of the thermodynamic features of various manifolds in the composition simplex obtained by processing direct VLE data can be used to supplement the adequacy of the model. For the cyclohexane–benzene–chlorobenzene system, the best NRTL equation parameters are those regressed from the extensive experimental VLE data available in the literature for the ternary system as a whole.